Pore filling behavior of YSZ under CMAS attack: Implications for designing corrosion‐resistant thermal barrier coatings. Issue 12 (5th June 2018) - Shan, Xiao; Luo, Lirong; Chen, Wenfu; Zou, Zhonghua; Guo, Fangwei; He, Limin; Zhang, Aiping; Zhao, Xiaofeng; Xiao, Ping
Abstract: To understand the pore filling behavior in thermal barrier coatings during calcium‐magnesium‐alumino‐silicate (CMAS) infiltration process, porous yttria‐stabilized zirconia pellets with different sizes of spherical pores were prepared to simulate thermal barrier coatings. The pores (D50 ranging from 6 to 77 μm) were introduced to the pellets using poly methyl methacrylate as pore forming agents. Then the pellets were sintered to remove the pore forming agents and to achieve a similar volume fraction of porosity with thermal barrier coatings. After CMAS infiltration, only some small pores in the CMAS‐infiltrated zones were filled by CMAS, whereas all large pores (larger than 13 μm) remained unfilled; besides, the results also show that even open pores can resist filling by CMAS. The reason may relate to pore diameters; if the diameter of a pore is relatively large, the pore surface will not be completely wetted by liquid CMAS, the liquid meniscus will be discontinuous, and therefore the pore cannot be filled. The key insight gained from this study is that introducing "CMAS‐proof" pores into thermal barrier coatings may be a potential way to mitigate CMAS damage.